2012
DOI: 10.1016/s1674-8301(12)60017-7
|View full text |Cite
|
Sign up to set email alerts
|

Cynodon dactylon and Sida acuta extracts impact on the function of the cardiovascular system in zebrafish embryos

Abstract: The aim of the present study was to screen cardioactive herbs from Western Ghats of India. The heart beat rate (HBR) and blood flow during systole and diastole were tested in zebrafish embryos. We found that Cynodon dactylon (C. dactylon) induced increases in the HBR in zebrafish embryos with a HBR of (3.968±0.344) beats/s, which was significantly higher than that caused by betamethosone [(3.770±0.344) beats/s]. The EC50 value of C. dactylon was 3.738 µg/mL. The methanolic extract of Sida acuta (S. acuta) led … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…rerio appear to have the capacity to double f H at 28° C. Embryonic f H for D . rerio at 28° C is around 238 beats min −1 (Kannan & Vincent, ), which is near the f Hmax measured here at 28° C, but resting f H decreases during development (Hu et al , ).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…rerio appear to have the capacity to double f H at 28° C. Embryonic f H for D . rerio at 28° C is around 238 beats min −1 (Kannan & Vincent, ), which is near the f Hmax measured here at 28° C, but resting f H decreases during development (Hu et al , ).…”
Section: Discussionsupporting
confidence: 75%
“…Neither Barrionuevo & Burggren (1999) nor Tsai et al (2011) measured f Hmax . Given the resting f H at 28 ∘ C is half the f Hmax (247⋅4 ± 4⋅5 beats min −1 ) measured in this study, D. rerio appear to have the capacity to double f H at 28 ∘ C. Embryonic f H for D. rerio at 28 ∘ C is around 238 beats min −1 (Kannan & Vincent, 2012), which is near the f Hmax measured here at 28 ∘ C, but resting f H decreases during development (Hu et al, 2000).…”
Section: Discussionsupporting
confidence: 64%
“…240 min −1 at 28°C and near 300 min −1 at 32°C. By comparison, Kannan and Vincent () also reported that resting f H in anaesthetised, embryonic zebrafish at 28°C was increased from around 140 to 238 min −1 by cardioactive drugs, suggesting that resting vagal tone can be appreciable in zebrafish. While we cannot be absolutely certain that MS‐222 did not affect T max and T arr data for f Hmax in killifish in our study, Jayasundara and Somero () also found that T arr was 0.2 − 1.9°C below CT max (for 26 and 9°C acclimated G. mirabilis , respectively) when conscious fish were acutely warmed.…”
Section: Discussionmentioning
confidence: 99%
“…In another study this effect was also attributed to its anti-arrhythmic activity [ 14 ]. The plant also increased heart beat rate in a study on zebrafish with a potency greater than that of betamethasone [ 15 ].…”
Section: Introductionmentioning
confidence: 99%